Hip and shoulder kinematics during initial sled acceleration in luging - A case study - Fedotova, V.; Pilipiv, V. (Human Movement, 2012)
The start is treated as one of the most important technical elements in all sliding sports, as it is the only phase when athletes can actively contribute to increasing sled velocity. Nevertheless, start kinematics in luging have seldom been addressed in literature. Therefore, the aim of this study was to analyse hip and shoulder movement of lugers during one of the essential start phases - the pull and push-off from the start handles - to further understanding of the velocity development process at its initial stage. Methods. Three experienced female lugers volunteered to take part in the case study. A number of start attempts were filmed and analysed using a motion tracking method. Results. The study found that an athlete and the sled do not move as a whole rigid system, and a hip movement relative to the sled was found to exist. The study participants used two techniques for achieving high sled velocity: by initially pulling on the start handles with a powerful back extension, and sliding the hips forward on the sled in an attempt to increase forward momentum; a combination of both techniques might provide increased performance. Athletes featured two weaknesses in terms of where horizontal sled velocity was lost - at the end of the initial pull on the handles and during the final moment of the push-off from the handles. The latter was previously believed to be another option at gaining increased sled horizontal velocity. Conclusions. As found in the results, athletes have at least two possibilities of increasing horizontal sled velocity. Hip movement relative to the sled appeared to be important for gains in velocity. Additional studies that analyse larger pulls are necessary for understanding the role of hip and sled relative movement in start technique and its impact on increasing initial velocity.